2020
DOI: 10.1002/app.49914
|View full text |Cite
|
Sign up to set email alerts
|

The influence of ceramic additives on intumescence and thermal activity of epoxy coatings for steel

Abstract: The article presents results of the research on the influence of graphite/kaolin and graphite/titanium oxide systems on thermal properties, intumescence degree and the integrity of the structure of intumescent protective films based on epoxy resins for steel. The TG/DTG/DSC analysis showed that graphite/kaolin system shifted the decomposition reaction of epoxy resin towards higher temperatures, even by about 30 C. Fire endurance tests and the SEM analysis confirmed these results because more thermally resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
(228 reference statements)
0
2
0
Order By: Relevance
“…The results of the study of the impact of the graphite system with kaolin and titanium oxide on thermal properties, the swelling degree, and the integrity of the structures protected by films based on epoxy resins were presented in [15]. Analysis of thermal gravimetry showed that the resulting systems shift the reaction of the epoxy resin decomposition toward high temperatures.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The results of the study of the impact of the graphite system with kaolin and titanium oxide on thermal properties, the swelling degree, and the integrity of the structures protected by films based on epoxy resins were presented in [15]. Analysis of thermal gravimetry showed that the resulting systems shift the reaction of the epoxy resin decomposition toward high temperatures.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Thermoplastic polymers tend to lead the additional process of flame spreading or propagation, instead of generating a pyrolysis gas directly from the sample surface to the condensed phase. During combustion, char-type flame retardants combine the fuel with non-pyrolytic carbon (char) to prevent fuel release and provide thermal insulation to the base polymer by forming a protective char layer [50][51][52][53][54][55][56]. In other words, the flame retardant causes charring on the polymer surface through dehydration of the flame retardant to generate double bonds in the polymer [57][58][59][60][61][62].…”
Section: Polymer Combustionmentioning
confidence: 99%